Study on comparison of bio-cocosand filter and biosand filter for drinking water treatment in rural area - Arjianah, Aliamat (2012)
Biosand Filter usually is used for household capacities since it is small, easy to build and maintenance but highly effective in purify water that have contaminant. Biosand filter is adapted from conventional slow sand filter for intermittent usage and it is suitable for the rural area, which their resident cannot afford to have a clean water supply. By using two Biosand Filter and one of them is integrated with raw coconut coir pith to increase the performance, the effectiveness to purify the untreated water can be determined by comparing the result testing for both filters. Recently, many researchers interested to conduct a study regarding coconut coir pith as one of the medium to purify the contaminant in water. Thus, in this study groundwater from Kg. Fajar 2, Gambang is treated using both filters since it contaminated by impurities and contain high level of heavy metal. Several testing is conducted on this groundwater such as pH, turbidity, E.Coli, total coliform, total dissolved solid, total suspended solid, dissolved oxygen and some of heavy metal which is iron, zinc, lead, manganese, copper, and chromium. Groundwater, which has been treated using both filters show impressive rate of reduction especially in bacteria and heavy metals removal as the result after the test is carried out. Based on Malaysia: National Guidelines for Raw Drinking Water Quality (Revised December 2000), the underground water from Kg. Fajar 2 is safe to be consumed after filtration using both of the filters.